Policy recommendations for improving academic achievement among IPLeiria student-workers - Lopes, Ana Sofia (2018)
In Portugal, student-workers represent 8.5% of higher-education students and observe higher dropout rates, partially because of a higher education system that is more fitted to the traditional students. Using an extensive longitudinal database with original information on individual, degree and employment characteristics of 1566 undergraduate studentworkers from IPLeiria, we determine the factors that drive the dropout and graduation risks of adult workers in higher education. We concluded that academic failure explains only a fraction of dropout behaviour among adult student-workers. Indeed, academic achievement is also affected by school-residence distance, financial difficulties, marital status, motivation, field of study, academic integration and professional background. We found that men are more likely to drop out and more influenced by employment variables (self-employment, job qualification and job-degree relation) while, for women, marriage (associated with household responsibilities) seems to increase the risk of dropout. Some policy recommendations are suggested for the higher education system to adapt better to the particular characteristics of adult workers, namely by: adjusting the schedule and composition of classes; appreciating the curriculum and orienting candidates, stopouts and poor performance students; providing scholarships; distributing the vacancies across admission regimes; and introducing shorter/simplified versions of the degrees.